Mobilities of iodide anions in aqueous solutions for applications in natural dye-sensitized solar cells. Issue 18 (1st May 2018) - Cassone, Giuseppe; Calogero, Giuseppe; Sponer, Jiri; Saija, Franz
Abstract : Dye-sensitized solar cells (DSSCs) composed of aqueous electrolytes represent an environmentally friendly, low-cost, and concrete alternative to standard DSSCs and typical solar cells. A joint experimental/computational study revealed the microscopic details behind the conduction properties of iodide anions in aqueous dye-sensitized solar cells. Abstract : Dye-sensitized solar cells (DSSCs) composed of aqueous electrolytes represent an environmentally friendly, low-cost, and concrete alternative to standard DSSCs and typical solar cells. Although flammable and toxic organic-solvent-based electrolytes have so far been employed more than simpler (iodide) aqueous solutions, recently recorded efficiencies of water-based DSSCs suggest a trend inversion in the near future. Here, we present a study, based on both experiments and ab initio molecular dynamics simulations, in which assessments on the efficiencies of three water electrolytes commonly employed in DSSCs ( i.e., LiI, NaI, and KI) are reported. In particular, by atomistically tracing the ability of the iodides as charge carriers and by experimentally measuring the generated currents, we demonstrate that NaI aqueous solutions are more efficient electrolytes than LiI and KI – in descending order – in transporting electrons in DSSCs under bias. Monitoring the role played by the hydration shells of the ionic species under an electric field, we interpret, by first-principles, the various iodide mobilities. This finding, when combined with general considerations on the cation-induced effects on the TiO2 electronic structure, is able to account for the distinct efficiencies of the investigated electrolytes.